2019
DOI: 10.1126/sciadv.aax4631
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric rivers drive flood damages in the western United States

Abstract: Atmospheric rivers (ARs) are extratropical storms that produce extreme precipitation on the west coasts of the world’s major landmasses. In the United States, ARs cause significant flooding, yet their economic impacts have not been quantified. Here, using 40 years of data from the National Flood Insurance Program, we show that ARs are the primary drivers of flood damages in the western United States. Using a recently developed AR scale, which varies from category 1 to 5, we find that flood damages increase exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 134 publications
(151 citation statements)
references
References 35 publications
(56 reference statements)
5
142
1
3
Order By: Relevance
“…Information from the National Flood Insurance Program (NFIP) claims and losses, available for the period 1978–2017, are used to identify historical California floods with substantial economic loss. We define the most damaging floods as events with insured losses in excess of $10 million as provided in Corringham et al (2019). In this study, we focus on floods affecting Northern California.…”
Section: Methodsmentioning
confidence: 99%
“…Information from the National Flood Insurance Program (NFIP) claims and losses, available for the period 1978–2017, are used to identify historical California floods with substantial economic loss. We define the most damaging floods as events with insured losses in excess of $10 million as provided in Corringham et al (2019). In this study, we focus on floods affecting Northern California.…”
Section: Methodsmentioning
confidence: 99%
“…An emerging area of research focuses on the intersection between the physical and human-related impacts associated with ARs. In the US West Coast, for example, flood damages linked to even a small increase in AR intensity can translate to large economic losses 152 . The interrelation between human activities, such as expansion of human development 153 and modification of surface processes, means that new approaches are needed to communicate AR impacts.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…Additionally, it has been shown that the lack of ARs is often correlated with drought periods (e.g., 6 ) . Their importance in extreme precipitation events and floods has been analyzed in some detail, mostly for the Western U.S., where ARs are the primary driver of damage caused by flooding 7 , and also in western Europe, where intense rainfall is strongly associated with ARs, their persistence being especially relevant as the precursors of winter floods 8 11 .…”
Section: Introductionmentioning
confidence: 99%